EVALUATION OF NUTRITIVE AND ANTI-NUTRIENT CONTENTS OF COMPOSITE MEAL FROM Sorghum bicolor (SORGHUM), Glycine max (SOYA BEANS) AND Sesame (BENNI SEEDS) - FALMATA, A. S.; SIHIYONA, E. W.; MARYAM, B. K.; BINTU, B. P.; SALAMATU, T.; CHAMBA, G.; MODU, S. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2021)
Composite meal is a meal made up of different classes of food such as carbohydrate, protein, lipids, which can be used for the management of Protein and Energy Malnutrition (PEM). The study evaluates the nutritive and anti-nutritive contents of composite meals produced from Sorghum, Soya beans and Benni seeds. The materials (sorghum, soya beans and benni seeds) used were purchased from Maiduguri Monday Market, Borno State, Nigeria. They were subjected to standard processing methods. The study investigated the proximate composition and antinutritional factors of the samples. Two different ratios used, were 60% and 50% sorghum, 40% and 30% soya beans and 20% benni seeds. The results of the proximate analysis revealed that there were significant (p<0.05) increases in protein, fat and fibre contents of the composite meal particularly, the 50:30:20 ratios; sorghum, soya beans and benni seeds respectively. The results of the anti-nutrient analysis showed a significant (p< 0.05) reduction in tannin and phytic acid in the composite meal. Based on the results obtained, the composite meal from sorghum, soya beans and benni seeds had a high nutritional value and can be used to ameliorate protein energy malnutrition.